Power Relations in Scorpio City by Mario Mendoza - Fuentes Bayona, Adriana Yiseth (Rastros Rostros, 2013)
Power is one of the most recurrent themes in the work of Mario Mendoza, and in the Colombian noir novel in general, since one of the characteristics of novels in this genre is social critique. Hence, this article conducts a hermeneutical analysis of power relations and mechanisms in Mario Mendoza’s novel Scorpio City, based on the study of power by French philosopher Michel Foucault. The analysis shows the underlying power structures in the religious, sexual and persuasive discourses that the hero of the novel comes into contact with.